2021
DOI: 10.1007/s00376-021-0317-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Distributions and Sources of Anthropogenic NMVOCs in the Atmosphere of China: A Review

Abstract: As the key precursors of O 3 , anthropogenic non-methane volatile organic compounds (NMVOCs) have been studied intensively. This paper performed a meta-analysis on the spatial and temporal variations of NMVOCs, their roles in photochemical reactions, and their sources in China, based on published research. The results showed that both nonmethane hydrocarbons (NMHCs) and oxygenated VOCs (OVOCs) in China have higher mixing ratios in the eastern developed cities compared to those in the central and western areas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 108 publications
2
4
0
Order By: Relevance
“…C 2 -C 4 alkanes mainly originate from the use and volatilization of NG/LPG [24], indicating that volatile chemicals from oil fields in DN exerted considerable influence on VOCs. Compared with summer (14-28%), the percentage of OVOCs was significantly lower in winter (3-11%), which is consistent with the findings of other regions [25]. It was found that photochemical reactions make an important contribution to the production of carbonyls [26], indicating that the photochemical reaction rate is lower in winter than in summer due to reduced solar radiation and lower temperature.…”
Section: Temporal Pattern Of Vocssupporting
confidence: 86%
“…C 2 -C 4 alkanes mainly originate from the use and volatilization of NG/LPG [24], indicating that volatile chemicals from oil fields in DN exerted considerable influence on VOCs. Compared with summer (14-28%), the percentage of OVOCs was significantly lower in winter (3-11%), which is consistent with the findings of other regions [25]. It was found that photochemical reactions make an important contribution to the production of carbonyls [26], indicating that the photochemical reaction rate is lower in winter than in summer due to reduced solar radiation and lower temperature.…”
Section: Temporal Pattern Of Vocssupporting
confidence: 86%
“…After the imposition of stringent stay-at-home policy, household volatile organic compounds (VOCs) concentrations reached the highest values compared to other periods, as residents spent longer time in their houses while activities outside home were restarted gradually during the re-opening stage [139]. The anthropogenic VOCs emissions-related residential environments during the lockdown may have had an impact on the total ozone formation potential in different areas [140]. Besides household air pollution deriving mainly from furniture, building materials, cooking, cleaning, lighting and heating activities, engineering system defects or presence of humidity, the increased use of disinfectant products, and lack of suitable ventilation routines and mechanisms rose the indoor pollutant concentrations of dwellings during the lockdowns, constituting those unhealthy and unsustainable environments [122,[141][142][143].…”
Section: Substantial Changes Of Ambient and Household Environmental Quality During Covid-19 Lockdownmentioning
confidence: 99%
“…Exposure to ambient particulate matter is one of the most important health risk factors [ 4 ]. It was estimated that approximately 4.2 million deaths were attributed to particulate matter air pollution all over the world in 2015 [ 1 ].These air pollutants can be generated from natural [ 5 ] and/or anthropogenic [ 6 , 7 ] sources [ 2 ]. Concentrations of air pollutants in ambient air are affected by two major factors, including emissions and meteorological conditions [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%